Aztec life - Clare, John D., 1952- (Hauppauge, N.Y. : Barron's Educational Series, 2000)
Text and illustrations cover ancient Aztec society, culture, art, religion, warfare, and institutions.
Includes index.
Young Adult
Keywords: Aztecs -- Juvenile literature; Aztecs; Aztecs